Effects of Phospholipase Dε Overexpression on Soybean Response to Nitrogen and Nodulation - Yao, Shuaibing; Wang, Geliang; Wang, Xuemin (Frontiers in Plant Science, 2022)
Nitrogen is a key macronutrient to plant growth. We found previously that increased expression of phospholipase Dε (PLDε), which hydrolyzes phospholipids into phosphatidic acid (PA), enhanced plant growth under nitrogen deficiency in Brassicaceae species Arabidopsis and canola. The present study investigated the effect of AtPLDε-overexpression (OE) on soybean (Glycine max), a species capable of symbiotic nitrogen fixation. AtPLDε-OE soybean plants displayed increased root length and leaf size, and the effect of AtPLDε-ΟΕ on leaf size was greater under nitrogen-deficient than -sufficient condition. Under nitrogen deficiency, AtPLDε-OE soybean plants had a higher chlorophyll content and activity of nitrogen assimilation-related enzymes than wild-type soybean plants. AtPLDε-OE led to a higher level of specific PA species in roots after rhizobium inoculation than wild type. AtPLDε-OE soybean plants also increased seed production under nitrogen deprivation with and without nodulation and decreased seed germination in response to high humidity storage and artificial aging. These results suggest that PLDε promotes nitrogen response and affects adversely seed viability during storage.